2018
DOI: 10.11114/jets.v7i1.3896
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Crossfit Training on Jump and Strength

Abstract: The purpose of this study is to investigate the effect of regular CrossFit training on some force and jump parameters. 32 healthy wrestling men participated in the study, 16 experimental and 16 control groups. For the experimental group, CrossFit training, known as Cindy, was practiced three times a week for 8 weeks. The training consisted of 5 bars, 10 push-ups and 15 squats for 20 minutes. The control group continued the classical wrestling practice. Myotest accelerometric system was used for measurements of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 11 publications
(11 reference statements)
0
6
0
1
Order By: Relevance
“…It has gained great popularity recently due to its short duration and effectiveness [4,8,25]. There are studies showing the effectiveness of a large number of Crossfit programs involving different exercises, set, repetition, and rest intervals [25,29]. Some Crossfit programs seem to be useful exercise programs due to the fact that they contain callisthenic exercises and are easily applicable and accessible [8,29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has gained great popularity recently due to its short duration and effectiveness [4,8,25]. There are studies showing the effectiveness of a large number of Crossfit programs involving different exercises, set, repetition, and rest intervals [25,29]. Some Crossfit programs seem to be useful exercise programs due to the fact that they contain callisthenic exercises and are easily applicable and accessible [8,29].…”
Section: Introductionmentioning
confidence: 99%
“…There are studies showing the effectiveness of a large number of Crossfit programs involving different exercises, set, repetition, and rest intervals [25,29]. Some Crossfit programs seem to be useful exercise programs due to the fact that they contain callisthenic exercises and are easily applicable and accessible [8,29]. Crossfit has been mostly preferred by recreational athletes to date, however future studies are needed to determine whether their impact on professional athletes is sufficient [12,25].…”
Section: Introductionmentioning
confidence: 99%
“…49 Yüksel et al stated that the 8-week Cindy CrossFit study was effective on jumping performance. 21 Sparkles and Behm reported that stable and unstable CrossFit methods provided similar improvement in jump performance. 50 In the study of Goins investigating the effects of 6-week CrossFit training on some physical and physiological variables, they reported that there was no effect on vertical jump values.…”
Section: Discussionmentioning
confidence: 96%
“…In the study of Goins conducted on some physical and physiological variables of 6week CrossFit training, they stated that there was a significant improvement in the deadlift, squat, and shoulder press values.17 Dilber and Doğru reported that CrossFitbased HIFT (high-intensity functional training) training was significantly effective on the right and left-hand claw strength, leg strength, and back strength in their study with the participants with an average age of 23.62 ± 5.39 years 20. Yüksel et al, stated that the 8-week Cindy CrossFit study was effective in strength development 21. Perna et al,…”
mentioning
confidence: 94%
See 1 more Smart Citation